Diskontinyuitas Sejarah Bali Abad XIX: Alternatif Mempelajari Masa Lampau melalui Pendekatan Postmodern - I Nyoman Wijaya (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
This study discusses the discontinuity of the history of Bali in the nineteenth century. The collapse of the Klungkung Kingdom in 1908, positioned as the present, serves as a starting point. It then moves backwards to 1849, which marked the beginning of the collapse of the Balinese kingdoms into the hands of the Dutch colonial government. Then it moves forward to form a periodization, but with a different frame of mind. The periodization is not connected to the present, but it is only used as a method to identify the location of historical discontinuities. The goal is merely to view whether an event brings new ideas that can make the old knowledge undergo ruptures, fractures, thresholds, accidents, and transformations. Using Foucault’s method of archaeology of knowledge combined with the theory of radical contingency, this study manages to demonstrate that the power after the fall of the Buleleng kingdom formed new knowledge which created the discontinuity of history in Bali in the nineteenth century.